1961
DOI: 10.1128/jb.82.1.135-141.1961
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION AND PRELIMINARY CHARACTERIZATION OF BACTERIOPHAGES FOR BACILLUS SUBTILIS

Abstract: Angeles), AND A. M. BRODETSKY. Isolation and preliminary characterization of bacteriophages for Bacillus subtilis. J. Bacteriol. 82:135-141. 1961.-A simplified procedure for direct isolation of phages for Bacillus subtilis from soil was developed. Phage enrichment was accomplished by growing streptomycin-resistant B. subtilis in medium previously inoculated with the soil sample. Contaminating soil bacteria were eliminated by adding bactericidal quantities of streptomycin and the phages were isolated by convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Southern analysis of the genome of this phage revealed that it shares significant homology with the virulent bacteriophage E79 . These data suggest that although UTl is apparently virulent on well-fed hosts, starvation conditions found in the aquatic habitat favour the establishment of a pseudolysogenic relationship between the bacteriophage and its host bacterium, much like the one described by Romig & Brodetsky (1961) in soil bacilli. In some aquatic environments as many as 45% of the presumptive P.…”
Section: Introductionmentioning
confidence: 65%
“…Southern analysis of the genome of this phage revealed that it shares significant homology with the virulent bacteriophage E79 . These data suggest that although UTl is apparently virulent on well-fed hosts, starvation conditions found in the aquatic habitat favour the establishment of a pseudolysogenic relationship between the bacteriophage and its host bacterium, much like the one described by Romig & Brodetsky (1961) in soil bacilli. In some aquatic environments as many as 45% of the presumptive P.…”
Section: Introductionmentioning
confidence: 65%
“…Although many phages infecting Bacillus spp. have been isolated (Romig and Brodetsky 1961;Ackermann et al 1978;Strauch et al 1989), B. cereus phages have not received much attention. This may be because disease caused by B. cereus is considered not as serious as that caused by other foodborne pathogens and other Bacillus spp., such as B. anthracis.…”
Section: Introductionmentioning
confidence: 99%
“…Certain virulent phages can exist inside dormant hosts in an arrested stage of the lytic cycle, which can resume when the host recommences vegetative growth. This state is known as pseudolysogeny [13].…”
Section: Introductionmentioning
confidence: 99%